2016
DOI: 10.1167/16.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement accuracy determines natural interception strategies

Abstract: Eye movements aid visual perception and guide actions such as reaching or grasping. Most previous work on eye-hand coordination has focused on saccadic eye movements. Here we show that smooth pursuit eye movement accuracy strongly predicts both interception accuracy and the strategy used to intercept a moving object. We developed a naturalistic task in which participants (n = 42 varsity baseball players) intercepted a moving dot (a "2D fly ball") with their index finger in a designated "hit zone." Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 67 publications
7
103
0
Order By: Relevance
“…The concurrence of eye movement separation time and hand movement onset is further evidence for common neural processing of action goals (e.g., Andersen and Cui, 2009; Crawford et al, 2004; Hwang et al, 2014). Moreover, our findings are closely related to the observation that eye and hand movements are interdependent during movement planning (Leclercq et al, 2013) and execution (Danion and Flanagan, 2018; Fooken et al; 2016, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The concurrence of eye movement separation time and hand movement onset is further evidence for common neural processing of action goals (e.g., Andersen and Cui, 2009; Crawford et al, 2004; Hwang et al, 2014). Moreover, our findings are closely related to the observation that eye and hand movements are interdependent during movement planning (Leclercq et al, 2013) and execution (Danion and Flanagan, 2018; Fooken et al; 2016, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…1B ). Stimulus velocity followed natural forces (gravity, drag force, Magnus force; Fooken et al, 2016). Launch angles were set to ±5°, ±7° (pass trajectories), ±10°, or ±12° (miss trajectories).…”
Section: Methodsmentioning
confidence: 99%
“…Saccade onsets and offsets were defined as the nearest reversal in the sign of acceleration on either side of the three-frame interval. 24 We then computed mean torsional eye velocity in the saccade-free time interval from pursuit onset to stimulus offset, and the number and amplitude of corrective saccades. Horizontal pursuit velocity and velocity gain were computed during steady-state pursuit (interval 200 ms after pursuit onset to stimulus offset) by dividing horizontal eye velocity by target velocity.…”
Section: Eye Movement Recordings and Analysismentioning
confidence: 99%
“…Most current models are 214 based on the idea that interception relies on measurements of kinematic variables 6,7,11,12,43 , such as 215 speed 6, 32, 44 , distance and/or depth 45 . This idea has also been used in experiments similar to ours where the 216 object moves behind an occluder 6,9,[46][47][48] . In those cases, it is assumed that humans estimate speed while 217 the object is visible and use that estimate to predict future position of the object behind the occluder.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with 276 numerous imaging and electrophysiological studies finding an important role for premotor and 277 supplementary motor areas in timing [57][58][59][60][61] . Alternatively, knowledge about movement durations may also 278 be used during movements although some studies have suggested that humans do not use timing 279 information when they have access to movement related state-dependent information 62, 63 . 280 some studies using more naturalistic paradigms or done with virtual reality 47,64…”
mentioning
confidence: 99%